PENGARUH KEPEMIMPINAN SERVANT TERHADAP KINERJA GURU DI SMP NEGERI 4 SENTANI. - Sigalingging, Berlian Novalita; Dwikurnaningsih, Yari; Sugiarto, Agus (Consilium: Education and Counseling Journal, 2025)
The purpose of this research is to evaluate the influence of servant leadership on teacher performance at SMP Negeri 4 Sentani. This research uses a quantitative approach through surveys involving the entire population of teachers at the school. Data were analyzed using linear regression and descriptive analysis after being collected through documentation, interviews, and questionnaires. The research results show that servant leadership as a principal has a positive and significant impact on teacher performance, with a coefficient of determination of 0.71. This leadership style greatly influences teachers' work motivation and their level of empowerment. Principals who implement servant leadership can create a supportive work environment, encourage collaboration, and enhance teaching innovation. However, issues such as time and resource constraints faced by school principals hinder the full implementation of this leadership model.